Penyampaian Informasi Pekerjaan Bagi Fresh Graduate Melalui Realistic Job Previews - Adi Wijaya; Frikson C Sinambela (Psikostudia : Jurnal Psikologi, 2021)
This field experiment review aim was to examine four hypotheses of Realistic Job Previews (RJPs) on 20 fresh graduates respondents. Declarative knowledge,  RJPs measurement scale, and interview was used as method of data gathering. The data results by using Mann-Whitney U Test showed that there is no significant relation (p = 0,462) among met expectation variable (p = 0,333), coping strategy (p = 0,462), honesty and integrity perception (p = 0,822) and likelihood to stay (p = 0,469). The research implications are if there is similarity between general expectation and reality of a job, and low possibility for the respondents to reject the job offer, then RJPs won’t give any positive and significant effect in pre-hire process.